Food Security Challenges Amidst Socioeconomic Instability - Adetayo Olorunlana; Eugene Osasumwen Bello; Nnenna Okorie-Eugene (Rowter Journal, 2025)
Global insecurity, encompassing political unrest, warfare, and environmental shifts, has a profound impact on food security, presenting significant challenges to global food systems. This review aims to examine the multifaceted effects of global insecurity on food sustainability, investigating the interconnected relationships between insecurity factors and food systems, while proposing potential solutions to mitigate these challenges. The review synthesizes insights from a range of academic journals, policy reports, and case studies, encompassing diverse geographic regions and types of insecurity relevant to food security. Global instability has detrimental effects on food production, distribution, and availability. Political unrest and conflicts lead to migration and the destruction of agricultural infrastructure, while climate change exacerbates food shortages through extreme weather events. Precision farming and genetically modified crops offer potential solutions but are dependent on significant investment and supportive policies. Effective policy interventions, including investments in agricultural infrastructure, social protection, and peacebuilding, are crucial for strengthening food systems. Global collaboration and resource sharing are key to the successful implementation of these strategies. Addressing food security amidst global instability requires comprehensive and coordinated efforts. Research into agricultural resilience, technological advancements, and the integration of social protection systems will be vital in fostering sustainable food systems that can withstand the pressures of global volatility.